Intestate Succession Rights of Surviving Spouse in Russia, France and Spain: Сomparative Legal Analysis - A. D. Fokina (Московский журнал международного права, 2018)
Introduction. Currently, the surviving spouse is a legal heir in the majority of the states of Romano-Germanic legal family, but the conditions for granting and the scope and types of rights of the surviving spouse in intestate succession simultaneously with the relatives of the testator and in their absence in Russian law and foreign laws vary significantly. In addition, in foreign countries, there is a tendency to change the understanding of marriage and family relations: a more important role was assigned not only to their formal securing, but also to the actual nature of the relationship between the spouses, which also affected the rights of the surviving spouse in intestate succession. These differences in the regulation of the intestate succession rights of the surviving spouse in Russia and foreign countries and the trends in the development of foreign legislation justify the relevance and need for a comparative legal analysis of the intestate succession rights of the surviving spouse in Russia and in other countries related to the Romano-Germanic legal family, which include, in particular, France and Spain. The purpose of this study was to find ways to improve current Russian law on inheritance (in particular, the surviving spouse’s intestate succession rights) on the basis of the comparative legal analysis of the statutory regulation of intestate succession in Russia, France and Spain. The study had the following objectives: to identify differences in the termination of marriage as an impediment for surviving spouse’s intestate succession in Russia, France and Spain; to determine the order of heirs which the surviving spouse occupies and his right to inheritance share in Russia, France and Spain, including his right to compulsory share; to identify the intestate succession rights of surviving spouse, other than his right to inheritance share, in French and Spanish laws for their further consideration as potential novels of Russian legislation on inheritance.Materials and methods. The material for this study was the legislation of Russia, France and Spain (in particular, the rules of inheritance, family and housing law), as well as scientific works of Russian and foreign experts in the field of inheritance law. The methodological basis of the research is represented by a complex of general scientific methods (analysis, synthesis, induction, deduction), as well as special methods used in legal science, such as historical-legal, formal-legal and comparative-legal methods.Research results. As a result of a comparative legal study, similarities and differences in the legal regulation of Russia, France and Spain were defined in such aspects of inheritance by law as the obstacles to surviving spouse intestate succession, the right of the surviving spouse to the inheritance share, including a compulsory share in the inheritance, as well as other rights that have complex nature and often differ from the rights to inheritance share (right to housing where the surviving spouse usually lived with the testator, right to receive allowance and right to home furnishings and belongings).Discussion and conclusions. As the main conclusions of the comparative legal analysis of intestate succession rights of surviving spouse in Russia, France and Spain the author proposes some amendments to Russian legislation on intestate succession.